Pengelolaan Event “Press the Button” PT. Inti Muda Kreasi atau Emvrio Production di Masa Pandemi Covid-19 - Gloria Renatha; Sinta Paramita (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The Covid 19 pandemic has hampered almost all activities or work. Starting from educational activities, office activities, etc. All people are forced to carry out all their activities at home. One type of business that has been affected by the Covid-19 pandemic is an event organizer. The existence of this pandemic limits human physical contact which requires that music events be stopped for several years. The event organizers also innovated to hold events online. However, over time, to improve the economy, the government allowed holding events offline. PT. Inti Muda Kreasi or Emvrio Production took the first step as the first event organizer to hold an offline event for the first time during a pandemic. The existence of the Press the Button event, as the first music event after the Covid-19 pandemic, has become a reference for other event organizers to create music events that can run smoothly and comply with existing health protocols. This thesis discusses how event organizers reassemble music events in the midst of the Covid-19 pandemic. Pandemi Covid 19 telah menghambat hampir seluruh kegiatan ataupun pekerjaan. Mulai dari kegiatan pendidikan, kegiatan perkantoran, dll. Seluruh masyarakat terpaksa harus melakukan seluruh kegiatannya di dalam rumah. Salah satu jenis usaha yang terkena dampak dari pandemi Covid-19 adalah event organizer. Adanya pandemi ini membatasi kontak fisik manusia yang mengharuskan event musik diberhentikan selama beberapa tahun. Para event organizer pun melakukan inovasi untuk mengadakan acara secara daring. Namun, seiring berjalannya waktu, guna memperbaiki perekonomian, pemerintah memperbolehkan penyelenggaraan acara secara luring. PT. Inti Muda Kreasi atau Emvrio Production mengambil langkah awal sebagai event organizer pertama yang mengadakan acara luring untuk yang pertama kalinya di masa pandemi. Adanya event Press the Button, selaku event musik perdana setelah pandemi Covid 19, menjadi acuan bagi event organizer lainnya untuk menciptakan event musik yang dapat berjalan dengan lancar serta patuh pada protokol kesehatan yang ada. Skripsi ini membahas bagaimana event organizer merangkai kembali event musik di tengah pandemi Covid 19.